Antimicrobial Efficacy of UV Radiation on Escherichia coli O157:H7 (EDL 933) in Fruit Juices of Different Absorptivities - Oteiza, Juan Martín (2005)
The efficacy of UV light for inactivating E. coli (ATCC 25922) and E. coli O157:H7 (EDL 933) was examined in fruit juices (orange, apple, and multifruit) with different absorptivities under several operating conditions (liquid film thickness and agitation rate). The juices were inoculated with two bacterial concentrations (10(5) and 10(7) CFU/ml) and were treated using a UV desinfection unit at 254 nm; UV doses ranged from 0 to 6 J/cm2. The effect of the culture medium, tryptone soy agar (TSA) and sorbitol MacConkey agar (SMAC), on the recovery of E. coli strains exposed to UV radiation was also analyzed. The most suitable culture medium for recovery of E. coli strains in juices exposed to UV radiation was TSA. Values of D (radiation dose [joules per square centimeter] necessary to decrease the microbial population by 90%) obtained in all juices assessed were higher in TSA than in SMAC. In the juices analyzed, stirring of the medium exposed to UV radiation and reducing liquid film thickness (to 0.7 mm) produced the highest bactericidal effect. A linear relationship was found between the D-values obtained and the absorptivity coefficients for all the juices. The higher the absorbance of the medium, the greater the values of D required to inactivate E. coli strains by UV radiation. An equation was developed to describe the relationship of the fraction of energy absorbed by the system (absorbed energy factor [AEF]), the thickness of the film exposed to UV radiation, and the absorptivity coefficient of the juices. A linear relationship was found between D and AEF in the different juices tested.